Differential prognostic impact of stratified additional chromosome abnormalities on disease progression among Malaysian chronic myeloid leukemia patients undergoing treatment with imatinib mesylate - Siti Mariam, Ismail; Norhidayah, Ramli; Zulaikha, Abu Bakar; Nazihah, Mohd Yunus; Rosline, Hassan; Kausar, Ghazali Anis; Sarina, Sulong; Azlan, Husin; Ankathil, Ravindran (Frontiers in Oncology, 2022)
Emergence of additional chromosome abnormalities (ACAs) in chronic myeloid leukemia (CML) patients during treatment with tyrosine kinase inhibitor (TKI) regime is generally associated with resistance to treatment and a sign of disease progression. We report the type, frequency and the differential prognostic impact of stratified ACAs with treatment response in 251 Malaysian CML patients undergoing TKI therapy. ACAs were observed in 40 patients (15.9%) of which 7 patients (17.5%) showed ACAs at time of initial diagnosis whereas 33 patients (82.5%) showed ACAs during course of IM treatment. In order to assess the prognostic significance, we stratified the CML patients with ACAs into two major categories - those with ACAs in the Ph positive cells and those with ACAs in Ph negative cells. In these two categories of patients, the ACAs were stratified into four major 4 groups. Group 1(+8/+Ph); Group 2 (hypodiploidy); Group 3 (structural/complex abnormalities); Group 4 (high risk complex abnormalities) and the association of the individualized groups with disease progression was assessed. In CML patients with ACAs in Ph positive cells, Group 1 and Group 2 relatively showed good prognosis while patients in group 3 and group 4 had progressed or transformed to AP or blast phase with median survival rate of 12 months after progression. Novel ACAs consisting of rearrangements involving chromosome 11 and chromosome 12 were found to lead to myeloid BP while ACAs involving the deletion of 7q or monosomy 7 led towards lymphoid blast phase. There was no evidence of group 2 abnormalities (hypodipoidy) contributing to disease progression. Compared to group 1 abnormalities, CML patients with group 3 and group 4 abnormalities showed higher risk for disease progression. In CML patients with ACAs in Ph negative cells, the association of the individualized four groups of ACAs with disease progression could not be assessed as none of them entered into disease progression. We conclude that the stratification and grouping of CML patients based on ACAs in Ph positive and Ph negative cells has differential prognostic impact and might be a potential risk predictive system to prognosticate and guide treatment at diagnosis and during treatment.